2012
DOI: 10.1063/1.4729774
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initio studies on Li doping, Li-pairs, and complexes between Li and intrinsic defects in ZnO

Abstract: First-principles density functional calculations have been performed on Li-doped ZnO using allelectron projector augmented plane wave method. Li was considered at six different interstitial sites (Li i), including anti-bonding and bond-center sites and also in substitutional sites such as at Zn-site (Li zn) and at oxygen site (Li o) in the ZnO matrix. Stability of Li Zn over Li i is shown to depend on synthetic condition, viz., Li Zn is found to be more stable than Li i under O-rich conditions. Hybrid density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…11,19 The Li Zn defect in ZnO has also been studied recently with several hybrid functionals. 3,[29][30][31] The polaronic structural distortion due to hole trapping has been reproduced in these studies. These results are a significant improvement over previous calculations using local density functionals.…”
Section: A Fully Localized Small Polaronsmentioning
confidence: 51%
“…11,19 The Li Zn defect in ZnO has also been studied recently with several hybrid functionals. 3,[29][30][31] The polaronic structural distortion due to hole trapping has been reproduced in these studies. These results are a significant improvement over previous calculations using local density functionals.…”
Section: A Fully Localized Small Polaronsmentioning
confidence: 51%
“…They also predicted that the Li Zn defect in ZnO may have a dual nature, where, in addition to the deep localized state, a shallow acceptor state may exist at about 0.21 eV above the valence band and be revealed in certain experimental conditions [18]. DFT calculations based on hybrid functional schemes predicted a binding energy of 0.75 eV [19,20] and 0.46 eV [21] for the Li Zn acceptor in ZnO. Carvalho et al [22] concluded that, by using different pseudopotentials and functionals, the calculated binding energy of the Li Zn acceptor varies between 0.6 and 1.1 eV.…”
Section: Introductionmentioning
confidence: 97%
“…One of the most challenging issues of ZnO lies in the difficulty of realizing efficient p-type conduction. Although quite a few reports claimed the realization of p-type ZnO films, and some optoelectronic devices have been demonstrated [6][7][8], the performance of such devices is still far below expectation. It is accepted that heterostructures constituted by alloyed semiconductor with different compositions can ensure efficient carrier injection and confinement, and thus may help to realize high-performance optoelectronic devices.…”
mentioning
confidence: 99%